Voter Education and the Fight Against Money Politics: Implementing Voter Education in the 2024 Indonesian Election - Tawakkal, George Towar Ikbal; Andrew D Garner; Thomas R Seitz; Andi Setiawan; Irma Fitriana Ulfah (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2025)
One of the persistent challenges in safeguarding democratic elections across many countries is the widespread practice of money politics, which primarily targets voters and undermines the core principles of democratic participation. While voter education is widely recognized as a crucial tool for promoting democratic integrity, existing literature offers limited analysis of its effectiveness in addressing money politics. This study seeks to fill that gap by examining the challenges faced in implementing voter education programs, focusing on their role in combating money politics. Adopting a mixed-methods approach, this research combines a systematic literature review, drawing exclusively from peer-reviewed domestic and international journals, with fieldwork conducted during Indonesia’s 2024 simultaneous elections in two regencies. Despite reports of rising money politics in the 2024 elections, various voter education initiatives were also deployed. However, the persistence of vote buying suggests these efforts have had a limited impact. Based on interview data and document analysis, the study identifies four primary obstacles to effective voter education: limited outreach and accessibility, inadequate and unengaging educational materials, a shortage of qualified facilitators, and a lack of contextual relevance for the target audience. These findings underscore an urgent need to redesign voter education strategies to be more inclusive, participatory, and tailored to local contexts. This research contributes to the growing discourse on electoral integrity by offering actionable insights for policymakers, electoral bodies, and civil society organizations working to strengthen democracy through informed and empowered voter participation.